Can we predict movie Revenue? - Ratnayake, M.P. (Faculty of Graduate Studies , University of Sri Jayewardenepura, 2018)
The movie industry is characterized with its unpredictability in success and failure. Predicting revenue of a particular movie has intrigued industry tycoons as well as scholar as a challenging problem. The cinema acts not only as a expressive artistic medium, but also serves as large scale industry that impact on the economy However some foreign scholars revealed that there are methodologies to forecast future revenue of the movies. Film revenue forecasting has been studied in variety of contexts ranging form easthetics economics, management to statistic and psychology. In this study author examines whether movie revenue can be predicted by using determinants like criticism, budget, propaganda directors creativity, star power and copies released to theaters. All the films screened in 2012 were selected, and collected data related to them. The number of copies released to theaters, propaganda expenditures and budgets were collected. Star power of 2012 film actors and actresses, were converted into mathematical figures. Also a scholarly panel was appointed to give grades to those stars and resultant figures were used for final calculating. Same process was used when calculating directors creativity. To calculate propaganda expenditure, financial figures as well as other scenarios like Contar deals, free interviews were used. sing regression model author founds that there is a correlation between revenue and those six determinants. In conclusion it can be said that using these determinants, movie revenue can be predicted. However this study only test six determinants, and there are some important determinants to be tested. The results can be further improved by incorporating more determinants and larger sample size in future studies.
Keywords: Movie, Revenue, Criticism, Budget, Propaganda